Urban Expansion patterns of choman city : A study in Urban Geography - Kamaran Wali Mahmod; Bzhar Abdulsatar Abdulqader (QALAAI ZANIST JOURNAL, 2022)
therhere Urban Expansion is considered one of the problems. The importance of this topic goes back to show the dangers of the Expansion city of Choman which affects farm lands, and the economic state of the country. The aim of this research is to showcase the pattern of Choman's Urban Expansion as well as specifying the stages of Choman's urban expansion. The research consists of an 1. introduction, 2.geographical places, 3.stages of Choman's urban expansion, and its 4.patterns as well as 5. the important factors playing a part in the expansion of Choman, the research was come to some results and conclusion such as the migration of the citizens from the village to the city of Choman. Is the main cause of the urban expansion. The patterns of urban expansion change from stage to stage but due to its geographical location, the expansion is pattern linear.